The outlook for Myanmar’s inorganic fertilizer use and 2021 crop harvest: An ex-ante assessment - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
International inorganic fertilizer prices and shipping costs substantially increased in 2021 compared to a year earlier. This will lead to significantly higher border prices for fertilizer in Myanmar, an important development as Myanmar imports almost all of its fertilizer from abroad. The impacts of the current political crisis on the local transport sector and the depreciation of the Myanmar currency, the kyat, will further increase domestic fertilizer prices. Based on a survey of agro-retailers in March 2021, fertilizer prices were estimated to be 22 percent higher for urea and 10 percent higher for compound fertilizer compared to the same period a year earlier. In addition to these supply-side challenges, effective demand for inorganic fertilizer is expected to be lower in 2021 due to significantly reduced farmer incomes, lower credit availability, and more uncertain agricultural profitability. Given these international and local developments, fertilizer use in Myanmar in 2021 will be substantially less than normal. Ex-ante simulations, which assume a ratio of additional crop output per unit of fertilizer applied between three and five, indicate that a reduction of fertilizer use–all else equal–in the country to half the level of a normal year would reduce agricultural output in 2021 by between 9 and 15 percent. Particularly, monsoon rice production will be affected. The Delta region produces half of Myanmar’s monsoon rice and uses about half of the inorganic fertilizer imported annually. Thus, the expected shocks to fertilizer markets in 2021 may have outsized effects on rice production levels in particular.